Entre telas, presenças e espaços: uma análise à luz da Teoria Iseriana sobre a relação texto-leitor em performances audiovisuais - Cordeiro, Alinne de Morais Oliveira (2022)
This dissertation investigates how spectators perceive their aesthetic experiences with artistic performances related to writing in a context of digital platforms. To this end, the study is supported by Literary Anthropology, by the Aesthetic Effect theory (ISER, 1996, 1999a, 1999b, 2013) and by Cultural Historical Theory. The intention did not start from what was proposed and affirmed by Paul Zumthor (2018) in Performance, Reception and Reading. Theoretical aspects of the presentation of the aesthetic effect and audiovisual supports with regard to the exhibition of the Aesthetic Effect live. Therefore, the problem that guides the research is: would the fact that a performance be watched through a video (and not live), would it hinder or even nullify the aesthetic experience for the listener? The work mapped the history and evolution of the relationship between poetry and performance, as well as its specificities, in addition to carrying out a contextual study regarding the Iserian theory and its recent updates. Still, it was developed as it develops (or not the feature in performances) developed in the YouTube comments. The methodology developed for the continuation of the research with the selection of the videos of O amor bate na aorta (DRUMMOND, 2012), by Drica Moraes; Elegia 1938 (DRUMMOND, 2012), performed by Caetano Veloso; If I were me (LISPECTOR, 1999), presented by Débora Wainstock and Geni e o Zeppelim (BUARQUE, 1978), staged by Letícia Sabatella. Then, a collection of comments and their analysis was carried out, organized according to the categories raised, directing us to a comparison of results. These useful procedures for visual response our hypothesis that support directly on aesthetics with performances, but not a point of contact with the novelty factor and were not a point of contact with the novelty factor and were presented. The work is meta-theoretical, as it proposes to understand and present conceptual alternatives about expectations with video performances.